Pre-competition weight loss models in taekwondo: Identification, characteristics and risk of dehydration - Janiszewska, K.; Przybylowicz, K. E. (Nutrients, 2020)
Athletes use different combinations of weight loss methods during competition preparation. The aim of this study was to identify and characterize pre-competition weight loss models, which describe these combinations. The second aim was to determine if any existing model pose a higher risk of severe dehydration and whether any of the models could be continued as a lower-risk option. The third aim was to explore whether athletes who used different weight management strategies could be differentiated based on age, sex, training experience or anthropometric parameters. Study participants were randomly selected from Olympic taekwondo competitors and 192 athletes were enrolled. Active (47% weight-reducing athletes), passive (31%) and extreme (22%) models have been described. In the extreme model, athletes combined the highest number of different weight loss methods (3.9 ± 0.9 methods vs. 2.4 ± 0.9 in active and 1.5 ± 0.6 in passive), reduced significantly more body mass than others (6.7 ± 3.5% body mass vs. 4.3 ± 1.9% and 4.5 ± 2.4%; p < 0.01) and all of them used methods with the highest risk of severe dehydration. The active and passive models could be continued as a lower-risk option, if athletes do not combine dehydrating methods and do not prolong the low energy availability phase. The extreme model carried the highest risk of severe dehydration. Every fifth weight-reducing taekwondo athlete may have been exposed to the adverse effects of acute weight loss. Taekwondo athletes, regardless of age, sex, training experience and anthropometric parameters, lose weight before the competition and those characteristics do not differentiate them between models.